2018
DOI: 10.1007/s40262-017-0620-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics and Pharmacodynamics of Evolocumab, a PCSK9 Inhibitor

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) increases plasma low-density lipoprotein cholesterol (LDL-C) by decreasing expression of the LDL receptor on hepatic cells. Evolocumab is a human monoclonal immunoglobulin G2 that binds specifically to human PCSK9 to reduce LDL-C. Evolocumab exhibits nonlinear kinetics as a result of binding to PCSK9. Elimination is predominantly through saturable binding to PCSK9 at lower concentrations and a nonsaturable proteolytic pathway at higher concentrations. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 53 publications
2
75
1
6
Order By: Relevance
“…The precision of the body weight covariate effects on CL and V max may have been influenced by the high correlation between individual random effects on CL and V max (Table 4 ). Baseline PCSK9 concentrations (~ 400 ng/mL) were small relative to mean observed unbound evolocumab C max of 18.6 or 59 µg/mL after 140 mg SC Q2W or 420 mg SC QM, respectively [ 34 ]. In the MM TMDD model approximation, k m represented the ratio of the sum of the complex internalization rate and dissociation rate constant to the drug-target dissociation rate constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precision of the body weight covariate effects on CL and V max may have been influenced by the high correlation between individual random effects on CL and V max (Table 4 ). Baseline PCSK9 concentrations (~ 400 ng/mL) were small relative to mean observed unbound evolocumab C max of 18.6 or 59 µg/mL after 140 mg SC Q2W or 420 mg SC QM, respectively [ 34 ]. In the MM TMDD model approximation, k m represented the ratio of the sum of the complex internalization rate and dissociation rate constant to the drug-target dissociation rate constant.…”
Section: Resultsmentioning
confidence: 99%
“…There was no evidence that anti-drug binding antibodies affected the PK profile, clinical response, or safety of evolocumab. Therefore, the incidence of anti-evolocumab binding antibodies is low, and not deemed necessary to evaluate in this analysis [ 34 ]. In addition, various analyses showed that evolocumab produced similar lipid-lowering effects in patients with and without diabetes, and hence not deemed a clinically relevant covariate in this analysis [ 35 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a combination therapy comprised of statins and ezetimibe has demonstrated the potential to overcome limitations of statin monotherapy via the inhibition of intestinal cholesterol absorption and the increase of cholesterol excretion [ 6 ]. In addition, a PSCK9 inhibitor, a suppresser of hepatic LDLR expression, has also indicated potential in non-statin hypolipidemic therapy [ 7 ]. Nevertheless, further improvement in therapeutic strategies is imperative for the fundamental regulation of hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…PCSK9 also inhibited ATP-binding cassette transporter A1 expression in macrophages by depleting LDL receptors, which reduced cholesterol efflux from lipid-laden foam cells [ 36 ]. Evolocumab was reported to facilitate the uptake of serum LDL-cholesterol by hepatocytes by inhibiting LDL-cholesterol receptor clearance [ 37 ], and promote ATP-binding cassette transporter A1 expression in macrophages by upregulating LDL receptor expression [ 36 ]. These findings suggest that evolocumab shrinks atherosclerotic plaques by reducing serum LDL-cholesterol concentrations and increasing cholesterol efflux from lipid-laden foam cells.…”
Section: Discussionmentioning
confidence: 99%